Efecto del lactosuero sumunistrado en forma líquida, como suplemento en la alimentación de pollos broilers, con raciones bajas en energía, en etapa de acabado - Amasifuen Armas, Adolfo (2010)
The following research was performed with aim to evaluate the effect of lactosuero, supplied in liquid form in drinking water as a supplement in feeding for broiler chickens: was used a completely randomized design (DCA), with four treatments (10% lactosuero, 15% lactosuero, 20% lactosuero and a control), and two repetitions, parameters evaluated were: initial weight, food consumption, water consumption, final weight, weight gain and feed conversion. In addition were used two different types of food: 20% of PT and 3200 Kcal / Kg. Containing fish meal as protein source, for the control treatment and 20% of PT and 28000 Kcal / Kg. Containing only soybean meal as protein source. For treatments (T1, T2, T3). The best rates for weight gain and feed conversion were recorded for T3 (20% lactosuero), with a weight gain of 1603.125 g. And feed conversion of 2.05, which do not differ statistically with the other treatments studied. These results implied that, lactosuero at a concentration of 20% satisfactorily compensated energy deficit levels of the ration and improved the quality and digestibility of vegetable protein. The feeding of broiler chickens supplemented with lactosuero in liquid form is well used by the birds, mainly by the energy benefits (lactose) and content (riboflavin) and vitamin B complex, very important in feeding the birds.